A Novel KPC Variant KPC-55 in Klebsiella pneumoniae ST307 of Reinforced Meropenem-Hydrolyzing Activity - Yoon, Eun-Jeong; Choi, You Jeong; Park, Sun Hee; Shin, Jeong Hwan; Park, Sung Gyun; Choi, Jong Rak; Jeong, Seok Hoon (Frontiers in Microbiology, 2020)
A novel Klebsiella pneumoniae carbapenemase (KPC) variant, KPC-55, produced by a K. pneumoniae ST307 strain was characterized. K. pneumoniae strain BS407 was recovered from an active surveillance rectal swab of a patient newly admitted to a general hospital in Busan, South Korea. Carbapenemase production was confirmed by the modified Hodge test, and the MICs of β-lactams were determined by the broth microdilution method. The whole genome was sequenced. Cloning and expression of the blaKPC–55 gene in Escherichia coli and MIC determination were performed. The enzyme KPC-55 was used for kinetic assays against β-lactams and compared with the KPC-2 enzyme. The new allele of the blaKPC gene had a T794A alteration compared to the blaKPC–2 gene, resulting in the amino acid substitution Y264N in the middle of the β9-sheet. Compared to the KPC-2-producing strain, the KPC-55-producing strain exhibited a lower level of resistance to most β-lactam drugs tested, however, the KPC-55 enzyme catalyzed aztreonam and meropenem at an increased efficiency compared to the catalytic activity of KPC-2. KPC subtypes could have varied phenotypes due to alterations in amino acid sequences, and such an unexpected resistance phenotype emphasizes the importance of detailed characterizations for the carbapenemase-producing Enterobacterales.